Inovasi Pengelolaan Pembiayaan di Pondok Pesantren Muhammad Al Fatih: Pendekatan Keuangan Berbasis Teknologi Aplikasi Akun.Biz - Muhammad Adi Susilo (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to analyze the implementation of a technology-based financial approach using the AKUN.biz application at the Muhammad Al Fatih Islamic Boarding School and its impact on efficiency and transparency in financing management. Through case study methods with in-depth interviews, observations, and document analysis, we explore how this technology changes how Islamic boarding schools manage their funds. The research results show that the use of the AKUN.biz application provides significant innovation in Islamic boarding school financing management. This system has increased efficiency by reducing errors that can occur due to manual recording. In addition, this approach also increases transparency by providing stakeholders with direct access to financial information. However, the research also identified several obstacles, such as limited infrastructure and technological understanding among Islamic boarding school administrators. Therefore, recommendations are made to improve data security and provide training on application use to administrators. In a broader context, this research contributes to developing more effective and transparent financing management in Islamic boarding schools. This will not only provide benefits for the Muhammad Al Fatih Islamic Boarding School but can also be a guide for other Islamic boarding schools who wish to adopt similar technology in managing funds.